TETRASPANINs in Plants - Reimann, Ronny; Kost, Benedikt; Dettmer, Jan (Frontiers in Plant Science, 2017)
Tetraspanins are small transmembrane proteins that laterally associate with each other and cluster with numerous partner proteins as well as lipids. These interactions result in the formation of a distinct class of membrane domains, the tetraspanin-enriched microdomains (TEMs), which influence numerous cellular processes such as cell adhesion and fusion, intracellular membrane trafficking, signaling, morphogenesis, motility as well as interaction with pathogens and cancer development. The majority of information available about tetraspanins is based on studies using animal models or cell lines, but tetraspanins are also present in fungi and plants. Recent studies indicate that tetraspanins have important functions in plant development, reproduction and stress responses. Here we provide a brief summary of the current state of tetraspanin research in plants.